Proceedings of the 2018 ACM Conference on Economics and Computation 2018
DOI: 10.1145/3219166.3219202
|View full text |Cite
|
Sign up to set email alerts
|

99% Revenue via Enhanced Competition

Abstract: A sequence of recent studies show that even in the simple setting of a single seller and a single buyer with additive, independent valuations over m items, the revenuemaximizing mechanism is prohibitively complex. This problem has been addressed using two main approaches:• Approximation: the best of two simple mechanisms (sell each item separately, or sell all the items as one bundle) gives 1/6 of the optimal revenue [BILW14].• Enhanced competition: running the simple VCG mechanism with additional m buyers ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…Our main result essentially achieves the greatly improved bound of [FFR18] (and improves it further) without losing any revenue: we prove a competition complexity bound of n(2 + ln(1 + m/n)). This guarantee is tight up to constant factors (and remains tight even if one is willing to lose an ε fraction), due to a lower bound of [FFR18].…”
Section: Connection To Related Workmentioning
confidence: 62%
See 3 more Smart Citations
“…Our main result essentially achieves the greatly improved bound of [FFR18] (and improves it further) without losing any revenue: we prove a competition complexity bound of n(2 + ln(1 + m/n)). This guarantee is tight up to constant factors (and remains tight even if one is willing to lose an ε fraction), due to a lower bound of [FFR18].…”
Section: Connection To Related Workmentioning
confidence: 62%
“…The two works most directly related to ours are [EFF + 17a] and [FFR18]. The one-sentence distinction between our results and these is that we strictly improve their main results regarding selling separately to additive bidders with independent items, but do not address alternative settings.…”
Section: Connection To Related Workmentioning
confidence: 74%
See 2 more Smart Citations
“…Roughgarden et al [16] showed a Bulow-Klemperer type result for matching environments. Eden et al [7] and Feldman et al [8] studied, for auctions selling multiple heterogenous items, the number of duplicate bidders needed for the VCG auction's revenue to approximate the optimal without duplicates. The bidders' preferences are i.i.d.…”
Section: Introductionmentioning
confidence: 99%